Evaluation of a Program of Aquatic Motor Games in the Improvement of Motor Competence in Children from 4 to 5 Years Old - Juan Ángel Simón-Piqueras; Alejandro Prieto-Ayuso; Elena Gómez-Moreno; María Martínez-López; Pedro Gil-Madrona (MDPI AG, 2022)
The present study aimed to verify whether a program of initiation to the aquatic environment composed of motor games (motor stories, learning environments and motor circuits) is more effective in the acquisition of aquatic skills in early childhood education than a traditional program. For this purpose, the Escala de Competencia Motriz Acuática for 4-5 year-old children was used before and after both programs. This scale has two factors, one named Familiarization, linked to more elementary aquatic abilities, and the Immersion factor, which integrates more advanced aquatic abilities. The two programs were used as independent variables, and there was a sample of 17 children over six weeks. The results show that both programs improved the acquisition of aquatic skills. The program that integrated motor games impacted the improvement of skills related to the Immersion factor significantly more.